How Could Models in Economics Possibly Provide ‘How-Actually’ Explanations? - Çevik, Dinçer (Problemos, 2025)
Much of the debate about model-based explanations in economics revolves around How-Possibly Explanations (HPEs). HPEs propose a potential way in which something could occur. I argue that these debates often occur without adequately considering the various ways in which economic models can provide How-Actually Explanations (HAEs). HAEs concentrate on what actually happens, providing explanations based on real-world events. I suggest that adopting a pluralistic and pragmatic approach is among the most effective methods for exploring the potential of HAEs in economics. To support my argument, I will use two case studies from microeconomics and macroeconomics. I contend that these case studies provide grounds to believe that a pluralist and pragmatist perspective could clarify how models in economics might offer HAEs.